Удосконалення технологічного процесу ремонту струмоприймача типу П-5 електровоза серії ВЛ11м в депо М - Німилович, Валерій Олегович; Nimylovych, Valerii Olehovych (Національний університет "Львівська політехніка", 2024)
Метою цієї кваліфікаційної роботи є удосконалення технологічного процесу ремонту струмоприймача типу П-5 електровоза серії ВЛ11м в депо М шляхом освоєння виготовлення конусних труб нижньої рами струмоприймачів типу П-5 електровозів ВЛ11м. Об’єктом дослідження є струмоприймач типу П-5 електровоза серії ВЛ11м. Предметом дослідження є удосконалення технологічного процесу ремонту струмоприймача типу П-5 електровоза серії ВЛ11м в депо М, освоєння виготовлення конусних труб нижньої рами струмоприймачів типу П-5. За результатами цієї кваліфікаційної роботи виконано такі завдання: - виконано аналітичний огляд конструкції електровоза серії ВЛ11м, в тому числі дахового обладнання електровоза; - проведено аналіз технічного стану та непланових ремонтів електровозів серії ВЛ11м; - проаналізовано діючу технологію ремонту струмоприймачів типу П-5, використання запасних частин при його ремонті; - розглянуто питання щодо освоєння виготовлення конусних труб нижньої рами струмоприймачів типу П-5 електровозів ВЛ11м; - розглянуто питання охорони праці для працівників, пов’язаних із ремонтом струмоприймачів, та надано рекомендації щодо їх покращення. Науково-практична цінність роботи полягає в комплексному підході до ремонту електровозів серії ВЛ11м в цілому із врахування як технічних удосконалень, так і економічних показників.

The aim of this qualification thesis is to improve the technological process of repairing the current collector of the type P-5 of the electric locomotive of the VL11m series in the depot M by mastering the manufacture of conical tubes of the lower frame of current collectors of the type P-5 of the VL11m electric locomotives. The object of the study is the current collector of the type P-5 of the VL11m series electric locomotive. The subject of the study is the improvement of the technological process of repairing the current collector of the type P-5 of the VL11m series electric locomotive in the depot M, mastering the manufacture of conical tubes of the lower frame of current collectors of the type P-5. According to the results of this qualification thesis, the following tasks were completed: - an analytical review of the design of the VL11m series electric locomotive was performed, including the roof equipment of the electric locomotive; - an analysis of the technical condition and unscheduled repairs of the VL11m series electric locomotives was performed; - the current technology for repairing P-5 type pantographs and the use of spare parts during its repair was analyzed; - the issue of mastering the manufacture of conical tubes of the lower frame of P-5 type pantographs of VL11m electric locomotives was considered; - the issue of labor protection for workers involved in the repair of pantographs was considered, and recommendations for their improvement were provided. The scientific and practical value of the work lies in the integrated approach to the repair of VL11m series electric locomotives as a whole, taking into account both technical improvements and economic indicators.
Improvement of the Technological Process for Repairing the P-5 Type Pantograph of VL11M Series Electric Locomotives at Depot M
Keywords: 6.273.00.02; технологія ремонту; непланові ремонти; електровози серії ВЛ11м; струмоприймач типу П-5; модернізація; випробування; розрахунок; repair technology; unscheduled repairs; electric locomotives of the VL11m series; P-5 type current collector; modernization; testing; calculation